THE RELATIONSHIP BETWEEN PRODUCT DIVERSITY AND THE PERFORMANCE OF CREDIT UNIONS AND BADAN USAHA KREDIT PEDESAAN IN YOGYAKARTA SPECIAL PROVINCE - Kusuma, Stephanus Eri; Jaya, Wihana Kirana (Journal of Indonesian Economy and Business, 2015)
This study analyzes the relationship between product diversity and the performance of microfinance institutions (MFIs), especially Credit Unions (CUs) and Badan Usaha Kredit Pedesaan (BUKPs) in Yogyakarta. It employs a binary logistic regression method in its analysis and utilizes annual pooled cross section data from 16 CUs and 34 BUKPs in Yogyakarta from 2011. The result indicated that there was a direct negative relationship between the levels of savingâloan product diversity and the scale of outreach and also between the levels of savingâloan product diversity and depth of outreach. It also suggested an indirect negative relationship between the levels of savingâloan product diversity and staff productivity and also between the levels of savingâloan product diversity and self-sufficiency.Keywords: product diversity, performance, microfinance institutions, CUs, BUKPs